2021
DOI: 10.1007/s10071-021-01503-6
|View full text |Cite
|
Sign up to set email alerts
|

Feline communication strategies when presented with an unsolvable task: the attentional state of the person matters

Abstract: Research on social cognitive ability in domestic cats is limited. The current study investigated social referencing in cats when exposed to first, a solvable, and then, an unsolvable scenario (i.e., reachable and unreachable treats) in the presence of either an attentive or an inattentive caregiver. Cats expressed more gaze alternation (P = 0.013), but less interaction with the caregiver (P = 0.048) and approached the treat container less frequently (P = 0.017) during the unsolvable test, compared to the solva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 55 publications
(85 reference statements)
1
13
0
Order By: Relevance
“…In support, almost all domestic species tested so far exhibit referential communicative behaviours towards humans 9 11 , 17 , 18 . Remarkably, however, all species for which referential communication with humans has been reported (dogs 17 , 19 , goats 9 , 20 horses 10 , 21 , cats 18 , dolphins 12 , wolves 22 , kangaroos 15 , non-human primates 8 , 13 ) use visual social signals efficiently and rely on them heavily for within-species communication and cooperation. This raises the alternative hypothesis that readiness for human-oriented referential communication may not emerge in species that lack certain species-specific characteristics such as the efficiency of intraspecific visual communication.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…In support, almost all domestic species tested so far exhibit referential communicative behaviours towards humans 9 11 , 17 , 18 . Remarkably, however, all species for which referential communication with humans has been reported (dogs 17 , 19 , goats 9 , 20 horses 10 , 21 , cats 18 , dolphins 12 , wolves 22 , kangaroos 15 , non-human primates 8 , 13 ) use visual social signals efficiently and rely on them heavily for within-species communication and cooperation. This raises the alternative hypothesis that readiness for human-oriented referential communication may not emerge in species that lack certain species-specific characteristics such as the efficiency of intraspecific visual communication.…”
Section: Introductionmentioning
confidence: 87%
“…But is domestication or intense human socialization a sufficient prerequisite? In support, almost all domestic species tested so far exhibit referential communicative behaviours towards humans [9][10][11]17,18 . Remarkably, however, all species for which referential communication with humans has been reported (dogs 17,19 , goats 9,20 horses 10,21 , cats 18 , dolphins 12 , wolves 22 , kangaroos 15 , non-human primates 8,13 ) use visual social signals efficiently and rely on them heavily for within-species communication and cooperation.…”
mentioning
confidence: 94%
“…Since then, variations of the ‘unsolvable task’ paradigm have been used in numerous studies to assess dogs’ cognitive abilities and to tease apart phylogenetic and ontogenetic effects on human-directed gazing in dogs, other canids (reviewed in Cavalli et al 2018 ; Mendes et al 2021 ), as well as other species (Alterisio et al 2018 ; Langbein et al 2018 ; Miklósi et al 2005 ; Pérez Fraga et al 2021 ; Zhang et al 2021 ). Several studies demonstrated that wolves show less ‘looking back’ than dogs do (Gácsi et al 2005 ; Marshall-Pescini et al 2017 ; Miklósi et al 2003 ; Udell 2015 ), while dingoes were found to show intermediate levels of human-directed gazing (Ballard et al 2021 ; Johnston et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cats have excellent social-cognitive abilities [ 3 ]. Furthermore, they can recognize human emotions (e.g., happiness and anger) from human communicative cues (e.g., the vocal tone and facial expressions of people) [ 4 , 5 ] and the state of attention and interest in themselves from a person’s gaze [ 6 , 7 ]. Previous studies have shown that cats increased ear and head movements upon hearing their owners’ voices, rather than the voices of others [ 8 ].…”
Section: Introductionmentioning
confidence: 99%